2018
DOI: 10.1523/jneurosci.0193-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

A Transient Developmental Window of Fast-Spiking Interneuron Dysfunction in a Mouse Model of Dravet Syndrome

Abstract: Dravet syndrome is a severe, childhood-onset epilepsy largely due to heterozygous loss-of-function mutation of the gene , which encodes the type 1 neuronal voltage-gated sodium (Na) channel α subunit Nav1.1. Prior studies in mouse models of Dravet syndrome ( mice) indicate that, in cerebral cortex, Nav1.1 is predominantly expressed in GABAergic interneurons, in particular in parvalbumin-positive fast-spiking basket cell interneurons (PVINs). This has led to a model of Dravet syndrome pathogenesis in which Nav1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
165
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(189 citation statements)
references
References 84 publications
23
165
1
Order By: Relevance
“…Notably, a study that performed electrophysiological recordings on acute brain slices from Scn1a ± mice found that, at later developmental stages, parvalbumin‐positive fast‐spiking basket cell interneuron excitability normalized. The results of this study implied that impairing action potential generation by parvalbumin‐positive fast‐spiking basket cell interneurons contribute to the initial epilepsy phenotype but may not be the sole mechanism that drives later, chronic epilepsy in DS . It is equally important, however, to consider that the variable severity and expressivity of the murine Scn1a ± epilepsy phenotype is highly strain dependent .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Notably, a study that performed electrophysiological recordings on acute brain slices from Scn1a ± mice found that, at later developmental stages, parvalbumin‐positive fast‐spiking basket cell interneuron excitability normalized. The results of this study implied that impairing action potential generation by parvalbumin‐positive fast‐spiking basket cell interneurons contribute to the initial epilepsy phenotype but may not be the sole mechanism that drives later, chronic epilepsy in DS . It is equally important, however, to consider that the variable severity and expressivity of the murine Scn1a ± epilepsy phenotype is highly strain dependent .…”
Section: Discussionmentioning
confidence: 82%
“…The results of this study implied that impairing action potential generation by parvalbumin-positive fast-spiking basket cell interneurons contribute to the initial epilepsy phenotype but may not be the sole mechanism that drives later, chronic epilepsy in DS. 47 It is equally important, however, to consider that the variable severity and expressivity of the murine Scn1a ± epilepsy phenotype is highly strain dependent. 48,49 Therefore, it will be interesting to explore whether stabilization of interneuron activity can be recapitulated in the zebrafish scn1lab wt/mut .…”
Section: Gliosismentioning
confidence: 99%
“…This extended period of protection after a single treatment suggests that ASO administration during a critical period of postnatal development might give long‐term seizure control in Dravet patients. A transient developmental window of interneuron dysfunction has been described in Dravet mice . Expansion of future testing of the Scn8a ASO to other seizure models will be of great interest.…”
Section: Resultsmentioning
confidence: 99%
“…A transient developmental window of interneuron dysfunction has been described in Dravet mice. 34 Expansion of future testing of the Scn8a ASO to other seizure models will be of great interest.…”
mentioning
confidence: 99%
“…Despite extensive studies of these models, the neuronal basis of Dravet and the mechanisms underlying the different stages are still debated, with evidence in favor of reduced function of inhibitory neurons, or enhanced function of excitatory neurons. In support of the "inhibitory neuron" hypothesis, electrophysiological studies demonstrated impaired firing of multiple types of inhibitory neurons during the worsening stage, with no apparent change in the excitability of excitatory neurons (De Stasi et al, 2016;Favero et al, 2018;Goff and Goldberg, 2019;Han et al, 2012;Ogiwara et al, 2007;Rubinstein et al, 2015bRubinstein et al, , 2015aTai et al, 2014;Tsai et al, 2015). Moreover, selective deletion of Scn1a in inhibitory neurons was sufficient to cause seizures and premature mortality Kalume et al, 2013;Kuo et al, 2019;Ogiwara et al, 2013;Rubinstein et al, 2015a).…”
Section: Introductionmentioning
confidence: 84%